Study of the Translation of Ecuadorian Idioms and their Equivalence Beyond Word Level. - Yela Gudiño, Daniela Eliud (2016)
As a result of their openness to international markets, more and more Ecuadorian writers, singers, songwriters, film makers and authors in general seek for the help of a translator before going to international audiences. An incredibly challenging issue for translators is to render the translation of all sorts of culturally bound words. When it comes to idioms, translators must determine whether there exists an equivalent for the intended message in the target text. The following paper studies the different strategies used to translate idioms and when to use them within the needs of the customer. However, usually it is merely the translators' decision to choose the best and most suitable way to convey meaning, even if it implies translating a phrase beyond word level.